Bridge Over Troubled Water: Perspective Connections between Coping and Play in Children - Capurso, Michele; Ragni, Benedetta (Frontiers in Psychology, 2016)
We propose that children’s play and coping strategies are connected. However, this connection has often been overlooked in the literature. To prove our hypothesis, the principal developmental functions of play are reviewed and compared with the different stages of the coping process. Our results show that coping and play are essential elements in child development, and indicate the presence of several overlapping areas where play and coping intersect. In spite of this, their interrelationship has seldom been examined. We explore the possible reasons for this omission with reference to the different natures of play and coping constructs, and also to the definitive psychometric and cognitive characteristics of most common coping measurement instruments. We conclude by proposing that play should be considered an elective form of coping in most aspects of children’s lives. We also propose that methods to measure coping in children should be improved and a more analogical approach should be adopted toward play to enable accurate recognition of coping.